Copaifera malmei Harms leaves infusion attenuates TNBS-ulcerative colitis through modulation of cytokines, oxidative stress and mucus in experimental rats. (1st March 2021) - Pavan, Eduarda; Damazo, Amilcar Sabino; Arunachalam, Karuppusamy; Almeida, Paulo Othávio de Araújo; Oliveira, Darley Maria; Venturini, Claudio Luis; Figueiredo, Fabiana de Freitas; Cruz, Thais Campos Dias da; Silva, Jéssica Vaz da; Martins, Domingos Tabajara de Oliveira
Abstract: Ethnopharmacological relevance: Ethnobotanical studies show that the infusion of the leaves from Copaifera malmei Harms (Fabaceae) has been utilized in the Brazilian traditional medicine to treat provocative and gastrointestinal diseases, among others. Recently, our research team has shown that an infusion extract of the leaves of C. malmei has a strong antiulcer activity and its oral use gives no indications of toxicity. Aim of the study: The aim of the study is to evaluate the anti-inflammatory intestinal effect of an infusion extract from the leaves of Copaifera malmei (IECm) in an animal model of ulcerative colitis induced by 2, 4, 6-trinitrobenzenesulfonic acid (TNBS). Materials and methods: Acute intestinal inflammation was induced in male Wistar rats by TNBS in 20% EtOH (0.25 mL). IECm was administered by oral gavage (for 72, 48, 24 and 2 h) preceding the induction of ulcerative colitis. The colon damage and degree of inflammation were evaluated by morphological observation scores and colon weight. The improved colonic mucosal injury, oxidative stress and inflammatory response were assessed by histopathological investigation and by estimating myeloperoxidase (MPO) activity, malondialdehyde (MDA) and glutathione (GSH) levels and tumor necrosis factor (TNF), interleukin 1β (IL1-β), IL-17 and IL-10 colon tissue concentrations. The histopathological changes were done on the colon tissues by hematoxylin and eosin and Periodic Acid-Schiff staining were utilized to measure the mucus. Results: Pre-treatment (25, 100 and 400 mg/kg) with IECm altogether diminished the intestinal inflammation prompted by TNBS in rats by diminishing colonic score by 69.12% ( p  < 0.01), 19.87% ( p  < 0.05) and 67.60% ( p  < 0.01), individually. Improvement of colonic mucosal injury by treatment with IECm was shown by a decline in MPO activity at dosages 25 and 400 mg/kg by 67.98% and 59.68% ( p  < 0.001), MDA levels 64.80% and 80.00% ( p  < 0.01) and an expansion in GSH content at all portions (62.53%, 53.38% and 81.20% p  < 0.05) compared with vehicle control group. IECm additionally prevention of intestinal inflammation as confirm by decreased cytokine levels, for example, TNF (31.26%, p  < 0.05, 50.68% and 45.95%, p  < 0.01), IL1-β (56.41%, 58.83% and 56.65%, p  < 0.001), IL-17 (51.66%, p  < 0.001, 22.23%, p  < 0.05 and 49.67%, p  < 0.001) and increased the IL-10 levels at 25 and 400 mg/kg (57.13%, p  < 0.01 and 35.83%, p  < 0.05) respectively. Histopathological examination of the colon tissue displayed recovery of ulcerative colitis of IECm treated animals by reducing leukocyte infiltrate, epithelial, submucosal and muscular layer damages and maintaining mucus production. Conclusion: These findings revealed that IECm was effective and possess anti-colitic activities in a rodent model of UC and can be useful in inflammatory bowel diseases (IBD). The pre-treatment with IECm decreased intestinal inflammation by reducing macroscopical and microscopical colon injury. In addition, the present study demonstrated that IECm ameliorates TNBS-colitis by promoting antioxidant effect, modulation of cytokines release and restauration of mucus production. The study reinforces the traditional use of the Copaifera malmei leaves infusion to inflammatory gastrointestinal disorders and makes IECm a potential herbal medicine for the treatment of IBD. Graphical abstract: Image 1 Highlights: IECm ameliorated ulcerative colitis induced by TNBS in rats. IECm exhibited antioxidant effect in TNBS-ulcerative colitis in rats. IECm decreased Th1 and Th17 cytokines and increased Th2 ones. IECm restored TNBS-induced mucus depletion in colonic tissue. IECm reduced histopathological changes induced by TNBS.